Challenges and Opportunities for Biomarkers of Clinical Response to AHSCT in Autoimmunity - Harris, Kristina M.; Lu, Tingting; Lim, Noha; Turka, Laurence A. (Frontiers in Immunology, 2018)
Autoimmunity represents a broad category of diseases that involve a variety of organ targets and distinct autoantigens. For patients with autoimmune diseases that fail to respond to approved disease-modifying treatments, autologous hematopoietic stem cell transplantation (AHSCT) following high-dose immunosuppressive therapy provides an alternative strategy. While more than 100 studies have been published on AHSCT efficacy in autoimmunity, the mechanisms that confer long-term disease remission as opposed to continued deterioration or disease reactivation remain to be determined. In a Phase II clinical trial, high-dose immunosuppressive therapy combined with autologous CD34+ hematopoietic stem cell transplant in treatment-resistant, relapsing-remitting multiple sclerosis (RRMS) resulted in 69.2% of participants achieving long-term remission through 60 months follow-up. Flow cytometry data from the 24 transplanted participants in the HALT-MS trial are presented to illustrate immune reconstitution out to 36 months in patients with aggressive RRMS treated with AHSCT, and to highlight experimental challenges inherent in identifying biomarkers for relapse and long-term remission through 60 months follow-up. AHSCT induced changes in numbers of CD4 T cells and in the composition of CD4 and CD8 T cells that persisted through 36 months in participants that maintained disease remission through 60 months. However, changes in T cell phenotypes studied were unable to clearly discriminate durable remission from disease reactivation after AHSCT, possibly due to the small sample size, limited phenotypes evaluated in this real-time assay, and other limitations of the HALT-MS study population. Strategies and future opportunities for identifying biomarkers of clinical outcome to AHSCT in autoimmunity are also discussed.